Correction of the Hindfoot Alignment after Supramalleolar Osteomy in Ankle Varus Deformity - A Three-Dimensional Analysis Using Weightbearing CT. Issue 1 (January 2022) - Burssens, Arne; Kvarda, Peter; Steiner, Caspar S.; Susdorf, Roman; Peterhans, Ursina; Krahenbuhl, Nicola; Barg, Alexej; Ruiz, Roxa; Hintermann, Beat
Category: Ankle; Ankle Arthritis; Hindfoot Introduction/Purpose: While correction of varus alignment at the level of the ankle joint has been investigated extensively after supramalleolar osteotomy (SMOT), the effect on the hindfoot alignment remains unclear. This can be attributed to the limitations of former 2-dimensional radiographic measurements used to quantify the complex 3-dimensional subtalar joint alignment. Therefore, we aimed to determine both the ankle and subtalar joint alignment before and after SMOT using a weightbearing CT and autogenerated 3-dimensional measurements. Methods: Twenty-seven patients with a mean age of 53 years (SD=10.1; range=25-73) were retrospectively analyzed in a pre- post study design using weightbearing CT images. Inclusion criteria were correction of ankle varus deformity by either an opening wedge (N=19) or dome osteotomy (N=8). Exclusion criteria consisted of an additional inframalleolar bony correction, i.e. calcaneal osteotomy or subtalar arthrodesis. Corresponding three-dimensional bone models were reconstructed to compute the autogenerated measurements: tibial anterior surface (TAS) -, tibiotalar surface (TTS)-, talar tilt (TT) - and talocalcaneal (TC) angle. Results: The pre-operative (TAS=86.9°, SD=4.9; TTS=79.8°, SD=5.6; TT=8.8°, SD=4.3) radiographic parameters of the ankle joint alignment improved significantly compared to the post-operative parameters (TAS=92.4°, SD=4.9; TTS=87.1°, SD=6.3; TT=5.1°, SD=2.7; P<0.05). (Fig. 1A) Radiographic parameters to assess the subtalar joint alignment improved significantly from preoperatively (TCax =42.8°, SD=9.3; TCsag=42.3°, SD=10.9; TCcor =29.5°, SD=11.8) to post-operatively (TCax =37.8°, SD=8.8; TCsag=39.1°, SD=10.6; TCcor=24.6°, SD=9.1; P<0.05). (Fig. 1B) Conclusion: A supramalleolar osteotomy is able to correct both the ankle and subtalar joint alignment. However, correction at the level of the subtalar joint accounted for only 3 to 4 degrees, which was less than found for the ankle joint alignment. For cases where a higher correction at the subtalar joint is necessary, we thus suggest adding a calcaneal osteotomy or subtalar arthrodesis to the SMOT.